A March to a Better World? Religiosity and the Existential Function of Belief in Social-Moral Progress. Issue 1 (2nd January 2016) - Rutjens, Bastiaan T.; van Harreveld, Frenk; van der Pligt, Joop; van Elk, Michiel; Pyszczynski, Tom
Abstract : This article reports an investigation of the existential function of belief in progress, specifically faith in social and moral advancement. We argue that for belief in progress to provide a sense of purpose and significance in our world, it must concern humanity and society and not merely the technological advances humankind accomplishes. We observed an effect of mortality salience on belief in social-moral (but not scientific-technological) progress, which was moderated by strength of religious belief. Participants low in religious belief showed an increase in belief in social-moral progress, while those high in religious belief did not. Follow-up analyses revealed that the latter finding was primarily due to Protestant participants, who scored highest on strength of religious faith and belief in inherent sin, and were the least optimistic about the future of humanity.